Estimated workload intensity during volunteer aquarium dives - Buzzacott, Peter; Grier, J.W.; Walker, J.; Bennett, C.M.; Denoble, P.J. (OXFORD UNIV PRESS, 2019)
Background: This study aimed to characterize the physiological demands of working dives on volunteer divers at a public aquarium in the USA. Aims: To estimate the workloads associated with volunteer dives in a US aquarium. Methods: Participants completed a medical and diving history questionnaire. Measurements included blood pressure before and after diving and continuous ECG (Holter) monitoring during diving. Dive profiles were recorded using loggers. Mean workload was estimated from total air consumption. Results Twenty-seven divers recorded 49 air dives over 5 days. Two-thirds were male and ages ranged from 40 to 78 years. Typically, each diver made two dives with a 30-60 min surface interval. Mean heart rate while diving was 100 beats per minute (bpm). Mean estimated workload during the dives recorded during this study was 5.8 metabolic equivalents (METS), with a range from 4.1 to 10.5. The highest mean recorded heart rate was 120 bpm over 40 min, vacuuming the floor in the shark exhibit. Conclusions: Given the mean age of this sample and the prevalence of cardiovascular risk factors (body mass index, high cholesterol and hypertension), it may be prudent for aquariums to regularly monitor SAC/kg and heart rate in volunteer divers, to identify which tasks require the highest workload intensity. Divers with existing cardiovascular risk factors might then be employed in dives with lighter workloads. In conclusion, volunteer dives at this aquarium required a mean workload intensity that was described by recreational divers as moderate. The highest workload, at 10 METS for 23 min, would be considered by many recreational divers as exhausting.